Speech Act of Suggestions in EFL Classroom Interactions: Teacher’s Politeness Strategies and Students’ Perceptions - Lintang Indah Ayu Respati Dewi; Sumardi Sumardi; Joko Nurkamto (Yayasan Visi Intan Permata, 2025)
In a classroom context, teachers are unavoidable to correct something that a student has said, done or written. Sometimes, the corrections are in the form of suggestions. However, giving suggestion can be challenging, as it can threaten the student’s negative face. To reduce this threat, politeness strategies are necessary. This study was conducted to (1) identify the types of politeness strategies employed by an EFL teacher in delivering suggestions, (2) examine students’ perception of their teacher’s politeness strategies. This research is a qualitative case study involving an English teacher and 34 eleventh-grade Senior High School students. Data were collected through observations and interviews, and then analyzed using Brown and Levinson’s politeness theory. The result revealed that the teacher employs a balanced combination of politeness strategies, with positive politeness, negative politeness, and off-record strategies each used 26% of the time, and bald on record used 22%. These strategies are employed for various reasons, including ensuring clear communication, maintaining a supportive classroom environment, and fostering closer teacher-student relationships. Additionally, students’ perceptions revealed that the teacher’s use of polite and indirect language contributes to a positive learning atmosphere, enhancing student comfort and engagement. However, this study is limited by its focus on a single teacher and a specific group of students, which may limit the generalizability of the findings to broader contexts.